Evaluation and validation of an RT‐PCR assay for specific detection of monkeypox virus (MPXV). Issue 1 (1st November 2022) - Paniz‐Mondolfi, Alberto; Guerra, Susana; Muñoz, Marina; Luna, Nicolas; Hernandez, Matthew M.; Patino, Luz H.; Reidy, Jason; Banu, Radhika; Shrestha, Paras; Liggayu, Bernadette; Umeaku, Audrey; Chen, Feng; et al.
Abstract: Monkeypox virus (MPXV) is a zoonotic orthopoxvirus within the Poxviridae family. MPXV is endemic to Central and West Africa. However, the world is currently witnessing an international outbreak with no clear epidemiological links to travel or animal exposure and with ever‐increasing numbers of reported cases worldwide. Here, we evaluated and validated a new, sensitive, and specific real‐time PCR‐assay for MPXV diagnosis in humans and compare the performance of this novel assay against a Food & Drug Administration‐cleared pan‐Orthopox RT‐PCR assay. We determined specificity, sensitivity, and analytic performance of the PKamp™ Monkeypox Virus RT‐PCR assay targeting the viral F3L‐ gene. In addition, we further evaluated MPXV‐PCR‐positive specimens by viral culture, electron microscopy, and viral inactivation assays. The limit of detection was established at 7.2 genome copies/reaction, and MPXV was successfully identified in 20 clinical specimens with 100% correlation against the reference method with 100% sensitivity and specificity. Our results demonstrated the validity of this rapid, robust, and reliable RT‐PCR assay for specific and accurate diagnosis of MPXV infection in human specimens collected both as dry swabs and in viral transport media. This assay has been approved by NYS Department of Health for clinical use.